Impact of Mobile Applications on Tourism Development in Uzbekistan - Karimov, Nodir; Kalandarova, Mekhribon; Makhkamova, Nodira; Asrorova, Zukhra; Saydamatov, Farkhod; Ablyakimova, Refide; Karshiboeva, Maftuna; Odilov, Bobir (Indian Journal of Information Sources and Services, 2024)
The rapid growth in mobile applications has completely transformed tourism globally, providing new tools and better opportunities to enhance experiences and accessibility for tourists. In Uzbekistan, with its great cultural heritage and historical sites, mobile applications can make a marked difference in the tourism sector by enhancing the engagement of tourists, improving the quality of services, and ensuring sustainability. The article explores the role of mobile applications in shaping the development of Uzbekistan's tourism industry by analysing how features like real-time information, booking services, and location-based recommendations make travelling smooth and personalised. It also discusses the challenges and opportunities regarding integrating mobile technologies into the country's tourist infrastructure, such as digital literacy, connectivity, and content issues. This present study, by case studies, end-user feedback, and industry data, points out the capacity of the mobile application to create more dynamic and accessible tourism in Uzbekistan for further economic development and increasing the country's attractiveness internationally.